The Influence Of Financial Literacy And Consumer Behavior On Consumer Decisions In Choosing Gopay As A Financial Technology Mobile Payment Application Using The Theory Of Reasoned Action For Gopay Users In Bandung City - Muhammad Azril Arya Kusuma; Brady Rikumahu (Telkom University, 2025)
This study was conducted to examine the influence of financial literacy and consumer behavior on consumer decisions to use gopay as a financial technology mobile payment application with the theory of reasoned action with the object of research being gopay users in the city of Bandung. This study uses a quantitative approach with a purposive sampling data collection method with a sample size of 100 respondents. Ordinal logistic regression analysis was used to analyze the data. The results of this study indicate that simultaneously financial literacy and consumer behavior have a significant effect on consumer decisions to use the gopay application as a mobile payment tool. Partially financial literacy does not have a significant effect on consumer decisions and consumer behavior has a significant effect on consumer decisions.